The relationship between ethics and innovation: specifically regarding the application and ethical considerations of artificial intelligence in animal models - Hong Yin; Qiannan Li; Shuling Yang; Chunhuan Zhang; Yueyi Zhai; Haowei Hou; Yan Qu (Holistic Integrative Oncology, 2024)
Abstract Objective To examine the role of animal models in tumor research, the ethical issues surrounding their use, and the potential of artificial intelligence technology in improving animal welfare and addressing ethical concerns. Methods This paper reviews the role of animal models in cancer research and considers the ethical issues surrounding their use. The various types and applications of animal models used in cancer research, as well as the controversy surrounding the use of experimental animals and the potential and feasibility of AI in improving animal welfare and addressing ethical issues, were examined in detail. Results Tumor animal models are a valuable research tool for advancing our understanding of tumor formation and for evaluating the efficacy of therapeutic approaches. The implementation of AI has the potential to diminish or supplant the necessity for animal experimentation, enhance the precision and credibility of research outcomes, and address ethical concerns. Conclusion Animal models are very important in tumor research, and they should be combined with the development of science and technology to improve animal welfare and relieve ethical pressure.